LEADERSHIP STYLE HEAD OF HEAD IN BONTORANNU VILLAGE MARISO DISTRICT MAKASSAR CITY - Oddang, Muh Raihan Saleh; Guntur, Muhammad; Darwis, Muh (Universitas Negeri Makassar, 2025)
This study aims to find out the Village Leadership Style in Bontorannu Village, Mariso District, Makassar City. This study uses a qualitative approach with a descriptive method. Data collection was carried out through observation, interview, and documentation techniques. The data analysis technique used in this study is interactive data analysis through the stages of data condensation, data presentation, and conclusion drawn. The results of the study show that the Village Leadership Style in Bontorannu Village, Mariso District, Makassar City, the village head in Bontorannu Village, Mariso District, Makassar City based on leadership style indicators (Kartono, 2018) has a good leadership style in decision-making ability, motivating ability, communication skills, responsibility, and emotional control ability. However, the village head in Bontorannu village, Mariso District still has a poor leadership style in the ability to control subordinates, this is because the village head does not rely too much on the position to force or rule his subordinates and focuses more on developing employee abilities and becoming an inspirational leader. Based on the description of indicators to see the leadership style of the village head, it can be concluded that the style of the village head of Bontorannu village in leading tends to use a democratic leadership style, besides that occasionally the village head of Bontorannu also uses a participatory leadership style